2001
DOI: 10.1073/pnas.051632898
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of contact sites in complex formation between transducin and light-activated rhodopsin by covalent crosslinking: Use of a photoactivatable reagent

Abstract: Interaction of light-activated rhodopsin with transducin (T) is the first event in visual signal transduction. We use covalent crosslinking approaches to map the contact sites in interaction between the two proteins. Here we use a photoactivatable reagent, N-[(2-pyridyldithio)-ethyl], 4-azido salicylamide. The reagent is attached to the SH group of cytoplasmic monocysteine rhodopsin mutants by a disulfideexchange reaction with the pyridylthio group, and the derivatized rhodopsin then is complexed with T by ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 35 publications
6
83
0
Order By: Relevance
“…3B shows the resulting geometry in the R*⅐G t [empty] complex. The model is in agreement with photo cross-linking experiments in which a photoactivated reagent attached at Ser-240 in loop C3 of R* cross-linked predominantly to G t ␣ sequence 342-345 (38). At the protein concentrations used in the experiment, a small fraction of the R*⅐G t ⅐GDP intermediate complex may have been present in equilibrium, explaining the second weaker cross-link to G t ␣ sequence 310-313 in these experiments.…”
Section: Coupling Between the R*/gt Interface And The Nucleotide Bindsupporting
confidence: 76%
“…3B shows the resulting geometry in the R*⅐G t [empty] complex. The model is in agreement with photo cross-linking experiments in which a photoactivated reagent attached at Ser-240 in loop C3 of R* cross-linked predominantly to G t ␣ sequence 342-345 (38). At the protein concentrations used in the experiment, a small fraction of the R*⅐G t ⅐GDP intermediate complex may have been present in equilibrium, explaining the second weaker cross-link to G t ␣ sequence 310-313 in these experiments.…”
Section: Coupling Between the R*/gt Interface And The Nucleotide Bindsupporting
confidence: 76%
“…Given the difficulties in applying conventional analytical approaches, such as NMR or X-ray crystallography, as a consequence of the insoluble and polymeric nature of PrP Sc , the design of novel, unconventional analytical approaches appears to be an attractive option. Our study shows that the combination of chemical crosslinking, proteolytic digestion, and mass spectrometry, an approach that has been applied to the structural study of other monomeric and polymeric proteins (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), can be successfully applied to PrP Sc . Using BS 3 , an agent that reacts primarily with amino groups, PrP 27-30 was readily crosslinked with formation of dimers, trimers, and higher-order oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…Using model proteins of known structure, it has been claimed that the method can be used, in conjunction with threading programs, to identify the fold of a protein (15). The method has been used to obtain valuable information about key features of unknown tertiary and quaternary structures of proteins (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). One particularly relevant example of the use of a variation of this approach was reported by Egnaczyk et al (24), who used it to probe the quaternary structure of -amyloid fibrils.…”
mentioning
confidence: 99%
“…Slessareva et al (71) have shown that the G␣ i1 ␣4 helix-␣4/␤6 loop are involved in 5-HT1a, 5-HT1b, and muscarinic M2 receptor interactions. For the rhodopsin⅐transducin (G␣ t ) complex, residues in the G␣ t ␣ 4 ␤ 6 loop (Arg-310 to Lys-313) were shown to cross-link with residues in the IC-3 loop of rhodopsin using a photoactivatable reagent, N-[(2-pyridyldithio)ethyl],4-azidosalicylamide (72). For the rat M3 muscarinic acetylcholine receptor (M3R)⅐G␣ q complex system, a cross-link has been reported between a D321C mutation on ␣ 4 ␤ 6 loop of G␣ q and a K7.58(548)C mutation on M3R.…”
Section: Discussionmentioning
confidence: 99%